Anticoagulant and anti-thrombotic therapy in acute type B aortic dissection: when real-life scenarios face the shadows of the evidence-based medicine - Pier Paolo Bocchino; Ovidio De Filippo; Francesco Piroli; Paolo Scacciatella; Massimo Imazio; Fabrizio D’Ascenzo; Gaetano Maria De Ferrari (BMC Cardiovascular Disorders, 2020)
Abstract Background Evidence-based recommendations about anticoagulation in acute type B aortic dissection (TBAD) are completely missing, but there is a diffuse conviction that it could prevent the healing process of the dissected aorta’s false lumen. However, several clinical conditions may lead to the necessity to start anticoagulant therapy among patients with acute type B aortic dissection, ranging from atrial fibrillation to more complicated clinical scenarios and the correct management in this kind of patients is still an open issue. Case presentation We are presenting a 51-years-old man with multi-infarct encephalopathy referred to us for an acute TBAD and a first diagnosis of ischemic cardiomyopathy complicated by left ventricular (LV) thrombus formation. Coronary angiography revealed a critical stenosis of left anterior descending artery (LAD) treated with drug-eluting stent deployment. The patient was addressed to triple antithrombotic therapy with acetylsalicylic acid, clopidogrel and warfarin with target INR 2.0–2.5. After 6 months, computed tomography angiography revealed the stability of the dissection flap. Cardiac magnetic resonance imaging, however, confirmed the persistence of a small thrombotic formation in LV apex, thus double antithrombotic therapy with warfarin and clopidogrel was instituted. The patient remained asymptomatic during the follow-up period but was advised to suspend his job and physical activities. Conclusion Current guidelines do not discuss anticoagulant therapy in the setting of TBAD and large randomized trials are lacking. Despite it is generally considered unsafe to administer anticoagulants in patients with TBAD, we present a case in which triple antithrombotic therapy was well tolerated and did not lead to progression of the intimal flap after 6 months.